What Does Moral Agency Mean for Nurses in the Era of Artificial Intelligence? - Ulrich, Connie M. (The Hastings Center report, 2026)
Being a moral agent was once thought to be an irreplaceable, uniquely human role for nurses and other health care professionals who care for patients and their families during illness and hospitalization. Today, however, artificial intelligence systems are often referred to as “artificial moral agents,” “agentic,” and “autonomous agents.” As these systems begin to function in various capacities within health care organizations and to perform specialized duties, the question arises as to whether the next step will be to replace nurses and other health care professionals as moral agents. Focusing primarily on nurses, this essay explores the concept of moral agency, asking whether it remains exclusive to humans or can be conferred on AI systems. We argue that AI systems should not supplant nurses’ moral agency, as patients come to hospitals or any other health care setting to be heard, seen, and valued by skilled professionals, not to seek care from machines.